Endowing Polythioester Vitrimer with Intrinsic Crystallinity and Chemical Recyclability. Issue 8 (13th March 2023) - Shi, Changxia; Zhang, Zhen; Scoti, Miriam; Yan, Xiao‐Yun; Chen, Eugene Y.‐X.
Abstract: Technologically important thermosets face a long‐standing end‐of‐life (EoL) problem of non‐reprocessability, a more sustainable solution of which has resolved to nascent vitrimers that can merge the robust material properties of thermosets and the reprocessability of thermoplastics. However, the lifecycle of vitrimers is still finite, as they often suffer from significant deterioration of mechanical performance following multiple reprocessing cycles, analogous to mechanical recycling, and they often show undesired creep under working conditions. To address these two key limitations, we have developed a cross‐linked semi‐crystalline polythioester with both dynamic covalent bonds and intrinsic crystallinity and chemical recyclability, affording a vitrimeric system that exhibits not only reprocessability and crystallinity‐restricted creep but also complete chemical recyclability to initial monomer by catalyzed depolymerization in solution or bulk. Therefore, reported herein is an "infinite" vitrimer system that is empowered with a facile closed‐loop EoL option once serial reprocessing deteriorates performance and the material can no longer meet the application requirements. Specifically, the polythioester vitrimer was constructed by copolymerization of a bicyclic thioester with a bis‐dithiolane, producing dynamically cross‐linked polythioesters with excellent property tunability, from amorphous to semi‐crystalline states and melting transition temperatures from 91 to 178 °C. Abstract : Running in circles : A high‐performance, reprocessable, creep‐resistant semicrystalline polythioester‐based vitrimer also exhibits complete chemical recyclability to initial monomer by catalyzed depolymerization in solution or bulk and the highly tunable thermal and mechanical properties.